Dampak Virtual Reality terhadap Identitas Individu dalam Novel Ready Player One Karya Ernest Cline - Jhodi Januarta; Fajar Permadi; Eva Dwi Kurniawan (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
Ernest Cline's novel Ready Player One depicts the impact of Virtual Reality (VR) on individual identity. The aim of this research is to analyze how VR is constructed as a space for testing individual identity in the novel Ready Player One. This research uses qualitative methods with a discourse analytic approach to examine how virtual identities are constructed in novels. Research data was obtained through novel analysis. Analysis was carried out by re-reading the novel and noting each scene that symbolized virtual identity. The research results show that Virtual Reality can be a place for individuals to experiment with their identity. In this novel, the main character Wade Watts uses an Avatar named Parzival to take part in a competition in the OASIS, a virtual world created by James Halliday. Wade chose this Avatar because he wanted to be a brave and strong figure, different from his true identity in the real world. Virtual Reality can have both positive and negative impacts on an individual's identity. On the one hand, Virtual Reality can be a place for individuals to experiment with their identity and find a more authentic identity. On the other hand, Virtual Reality can also influence individual identity by creating false and unrealistic virtual identities.